Redesign Economic Empowerment of Street Food Seller in Covid-19 Pandemic Periods: The Role of Digitalization - Rahmawati Rahmawati; Alfian Budi Primanto (Universitas Brawijaya, 2021)
Covid-19 has a very significant effect on business. Learning from the home policy since implemented during covid-19 made street food sellers around the school environment bereave potential income. The service community program aims to redesign economic empowerment street food sellers around the school environment to retrieve their lost income due to covid-19. There are three problems faced: human resources, production, and marketing. Community services program using Plan-Do-Study-Action (PDSA) Cycle proposed by Moen and Norman (2010) to accomplish the problem. The result shows that there is a positive trend of increasing income. Digital marketing strategy is the primary key to achieving the economic empowerment of food street sellers around the school environment. The new menu offered became a magnet that could attract new consumers and word of mouth as the practical marketing tools in rural areas.